Effects of Two Pre-germinated Brown Rice of Thailand on Postprandial Blood Glucose and Insulin Responses in Type 2 Diabetes - Boonpattararuksa, Jariya; Songchitsomboon, Sriwatana; Akkaravessapong, Pakinee; Wongpiyachon, Sunanta; Wasusun, Angsutorn; Komindr, Surat (Food and Applied Bioscience Journal, 2017)
Effect of two pre-germinated brown rice (PGBR) of KhaoDawkMali105 (KDML105) and glutinous rice RD6 (GRD6) on postprandial blood glucose, insulin and lipid concentrations were compared with glucose solution (50 g in 150 mL of drinking water) in 11 subjects with type 2 diabetes. All rice samples contained 50 g of digestible carbohydrates. The study was single-blind, randomized block design in which subjects participated in three separate 4 hour meal tolerance test. On test day, they ingested each test rice sample with steamed garlic-chicken, following 150 mL of drinking water in 15 min. Venous blood sample were collected in fasting subjects and at 30, 60, 90, 120, 180 and 240 min after starting to eat. The incremental areas under the curve (IAUC) of postprandial plasma glucose (PPG) and serum insulin response, glycemic index (GI) and insulin index (II) values were determined. Results showed that PGBR-KDML105 had mean values of PPG at 30and 60 min significantly lower (p<0.05) than glucose at the same time whereas PGBRGRD6 had mean values of PPG only at 60 min significantly lower (p<0.05) than glucose. Mean value of IAUC-glucose of PGBR-KDML105 were also lesser than PGBR-GRD6 but not significant. PGBR-KDML105 had a medium GI = 66.0, while PGBR- GRD6 had a high GI = 71.5 which not significantly different from PGBR-KDML105 but significantly lower (p<0.05) than glucose. There were no significant differences in mean values of IAUC-insulin, II and lipid profiles among two PGBR and glucose. In conclusion, consumption of PGBR-KDML105 will be more health benefits than PGBR-GRD6